Ethnic Variability in the Perception of Postoperative Pain In Jos, Plateau State, Nigeria - M, Usman Y.; I, Shugaba A.; I, Zoakah A. (Darul Yasin Al Sys, 2024)
Background: Postoperative pain management is crucial to patient care and recovery after surgery. Effective pain control not only alleviates suffering but also facilitates quicker recovery, reducing the risk of complications such as chronic pain syndromes. By identifying ethnic differences in pain perception, healthcare providers can tailor their pain management strategies better to meet the needs of patients from diverse cultural backgrounds. This study therefore sought to determine and compare baseline and serial postoperative pain scores using a visual analogue scale among non-indigenous (Fulani, Hausa, Igbo, and Yoruba) and Indigenous ethnic groups (Berom, Tarok, Ngas, and Mwagavul) in Plateau State, Nigeria. Materials and Methods: This was a comparative cross-sectional study conducted among 88 adults of Indigenous and non-indigenous ethnic groups of Plateau State at the Jos University Teaching Hospital (JUTH) recruited through stratified random sampling. The equal proportion allocation technique was employed for gender and ethnic groups. Ethical clearance, informed verbal and written consent were obtained before the commencement of the study. Baseline pain scores were determined by a pressure algometer. A pressure of 20N was applied bilaterally on the trapezius muscle between the C7 spinous process and the acromial process, and then the subjects were asked to rate the pain they felt on a numeric rating scale (NRS). The average NRS score was taken as the baseline pain score. Serial 2-hourly postoperative pain scores were also assessed in the immediate 24-hour postoperative period. All analyses were conducted using Statistical Package for Social Sciences version 23 (SPSS Inc., Chicago, IL, USA). Significance was set at the α = 0.05 level. Results: A total of 88 patients participated in this study with an equal number of gender and ethnic group representation. The median (IQR) age of study participants was 21 (19.2–35.6) years. No significant statistical difference in median baseline pain scores between the entire indigenous (21.5) and non-indigenous (21.0) ethnic groups, U = 0.64, p = 0.22. There was a statistically significant difference in baseline median pain scores between females (3.5) and males (2.0), U = 3.0, p = 0.036 in the indigenous and females (3.0) and males (2.0) in the non-indigenous ethnic groups, U = 3.9, p = 0.013. This study revealed a statistically significant difference in the median serial postoperative pain scores in the different specific Indigenous ethnic groups (H (2) = 24.2, p = 0.001) and the different specific non-indigenous ethnic groups (H (2) = 24.8, p = 0.001) as well. Conclusion: This study has demonstrated ethnic and gender variability in the perception of pressure and postoperative pain among different ethnic groups resident in Plateau State. Clinicians need to be aware of the fact that different ethnic groups in Plateau State perceive pain differently and put it into consideration when treating pain.